A novel fluidized bed "thermochemical battery" for energy storage in concentrated solar thermal technologies. (15th May 2021) - Padula, Stefano; Tregambi, Claudio; Solimene, Roberto; Chirone, Riccardo; Troiano, Maurizio; Salatino, Piero
Graphical abstract: Highlights: A new fluidized bed autothermal reactor is modelled for solar calcium looping process. Autothermal operation reduces the power requirement for the solar collection facility. The thermochemical battery operation is described for solar energy storage/release. Effect of design and operative variables on reactor performance is assessed. Charge efficiency of 90% (900 °C) and discharge efficiency of 80% (650 °C) are foreseen. Abstract: Thermochemical energy storage is gaining widespread consideration to increase energy dispatchability in concentrating solar thermal power plants. Accordingly, excess solar energy input drives an endothermic reaction, accomplishing high energy densities and virtually unlimited storage times. As gas–solid reactions are usually involved, multiphase reactor design is essential for the success of this technology. A novel concept of directly-irradiated fluidized bed autothermal reactor is investigated for applications in concentrated solar thermal technologies. The device can be operated as a rechargeable battery, alternating a charge phase, during which solar energy is collected and stored by an endothermal gas–solid reaction, and a discharge phase, during which the stored chemical energy is released by the reverse exothermic reaction. The autothermal operation, during the charge process, consists in the recovery of the sensible heat of the reaction products to preheat the reactants by means of an internal double-pipe countercurrent heat exchanger. This operation allows to increase the overall efficiency, reducing the required solar energy input. A compartmental model to simulate the operation of the thermochemical battery is developed and closed with constitutive equations and parameters obtained by previous experimental studies on lab-scale test facilities. Limestone calcination/carbonation has been considered as model reversible reaction. Both the charge and the discharge steps were assessed investigating the effect of the design and operational variables. For the charge operation, an optimal temperature was found around 900 °C with thermal efficiencies close to 90%. For the discharge operation, thermal efficiency was found to depend almost solely on the reactor temperature, reaching values as high as 80%, whereas the gas flowrate can be set independently. The upper limit for reaction temperature is set to the reaction equilibrium condition corresponding to the inlet concentration of carbon dioxide. The obtained results represent the basis for the realization of a new prototype, that will serve for the complete proof-of-concept of the directly-irradiated fluidized bed autothermal reactor.